2021
DOI: 10.3390/cancers13081835
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Expression of Th1- and Treg-Associated Chemokine Genes and CD4+, CD8+, and Foxp3+ Cells in the Premalignant Lesions of 4NQO-Induced Mouse Tongue Tumorigenesis

Abstract: Chemokines and cytokines in the tumor microenvironment influence immune cell infiltration and activation. To elucidate their role in immune cell recruitment during oral cancer development, we generated a mouse tongue cancer model using the carcinogen 4-nitroquinoline 1-oxide (4NQO) and investigated the carcinogenetic process and chemokine/cytokine gene expression kinetics in the mouse tongue. C57/BL6 mice were administered 4NQO in drinking water, after which tongues were dissected at 16 and 28 weeks and subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…It was reported that MDSCs were capable of inducing Treg, 34 which might result in a positive feedback loop that augmented immunosuppression. These findings were consistent with a recent study 35 . In addition, we found that the expression of CTLA‐4 on T cells and the proportion of Treg increased significantly after anti‐PD‐1 therapy, which may offset the effect of therapy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was reported that MDSCs were capable of inducing Treg, 34 which might result in a positive feedback loop that augmented immunosuppression. These findings were consistent with a recent study 35 . In addition, we found that the expression of CTLA‐4 on T cells and the proportion of Treg increased significantly after anti‐PD‐1 therapy, which may offset the effect of therapy.…”
Section: Discussionsupporting
confidence: 93%
“…These findings were consistent with a recent study. 35 In addition, we found that the expression of CTLA‐4 on T cells and the proportion of Treg increased significantly after anti‐PD‐1 therapy, which may offset the effect of therapy. These results suggested that PD‐1 blockade combined with CTLA‐4 blockade and Treg clearance may display a better therapeutic effect.…”
Section: Discussionmentioning
confidence: 77%
“…Tumor-infiltrating lymphocytes are an important prognostic factor for cancer progression and a key player in cancer immunotherapy. CCL2, CCL17 and CCL22 are cytokines with a role in T-cell recruitment [ 59 , 60 ]. Despite the role of CCL2 in recruiting both cytotoxic T cells (CTL) and monocytes to tumor sites [ 61 , 62 ], studies have shown that enhancement of the CCL2/CCR2 axis [ 63 ] or inhibition of CCL2 nitration [ 64 ] in antitumor therapy significantly promotes T-cell infiltration and exerts antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,35 In addition to the cell types mentioned above, other immune cell types are also relevant for different diseases. 3641…”
Section: Discussionmentioning
confidence: 99%